Kajian Kerentanan Beras Dari Padi Gogo Lokal Jambi Terhadap Sitophilus oryzae L. (Coleoptera: Curculionidae) - Siti Fanda Rini; Hendrival Hendrival (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2017)
The research was aimed to determine the susceptibility level rice from the local gogo rice of Subdistrict Tengah Ilir, District Tebo, and Province Jambi to an infestation of S. oryzae pest. The results showed that rice from varieties Tuo and Seribu Naik belong to a category moderate, while rice from varieties Tapang Bedaro and Cemplok belong to a category moderate-susceptible. Rice from varieties Kuku Balam, Rias Besar, Rias Kecil, Korok, Bedaro, Nartih, and Bungin are classified as susceptible to S. oryzae pest infestations. The result of correlation analysis showed that there was a significant positive correlation between susceptibility index with length rice (r= 0.906**, P<0.01) and shape rice (r= 0.771**, P <0.01) and there was a significant negative correlation with the wide of rice (r= -0.630*, P <0.05). The susceptibility index was also affected by the number of F1 S. oryzae (r= 0.922**, P <0.01) and a negative correlation was significant with the median development time S. oryzae (r= -0.912**, P<0.01). Dimensions rice such as length rice (r= 0.898**, P<0.01), shape rice (r= 0.911**, P<0.01), and wide rice (r= -0.816 **, P<0.01) also affects the number of F1 S. oryzae of emerging. The dimension of rice is a source of susceptibility to rice against S. oryzae pests.